PENGARUH TERAPI MUROTTAL TERHADAP PERUBAHAN SKOR KECEMASAN IBU BERSALIN KALA I FASE LATEN - Trisetiyaningsih, Yanita; Wulansari, Arista; Very Anto, Yuni (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: The first stage of childbirth begins since the beginning occurrence contraction of the uterus which causes depletion and the opening of cervix gradually until it reaches in an opening complete (10 centimeters). The opening of the cervix in the childbirth first stage of latent phase reach the size of diameter 1?3 centimeters or under 4 centimeters require time almost or until 8 hours. The one that affects the process of which influence childbirth is psychological in the forms of anxiety. One of the non-pharmacological therapy that can be done to reduce anxiety is murottal therapy. Objective: Knowing the influence of murottal therapy to changes of anxiety score childbirth mother?s at first stage of latent phase in Nur Hidayah, Bantul. Methods: The type of this is a pre-experimental research, using the method Quasi-Experimental with One Group Pre-test and Post-test Without Control Group Design approach. The sample of this research is childbirth mothers at first stage of latent phase with involves 32 respondents. Retrieval sample is done with using a Purposive Sampling Technique. Measurement the anxiety of this study using a Z-SRAS (Zung Self- Rating Anxiety Scale) questionnaire. The statistical test uses Paired Sample T Test. The murottal therapy in this research using QS. Ar-Rahman (1-78 verse) for 25 minutes with the reciter Mishary Bin Rashid Alafasy through an MP3 and earphone. Result: The result of the statistical analysis of Paired Sample T Test has shows that the average of anxiety childbirth mother?s at first stage of latent phase before given a murottal therapy was 48,84 and average anxiety after being given a murottal therapy was 38,91. The value of the average (mean) changes score anxiety pretest and posttest the granting of murottal therapy of 9,938. Obtained index difference (t) of the count 5.389 with value significance (p) 0.001. Conclusion: There is the influence of murottal therapy to changes of anxiety score of childbirth mother?s at first stage of latent phase in Nur Hidayah Hospital, Bantul. Keywords: Murottal Therapy, Anxiety, The First Stage of Latent Phase.